Nutritional and Agronomical Performance of Five Rice Varieties Cultivated in Saline Soils Amended with Leonardite - Reina Medina Litardo; Sady García Bendezú; Manuel Carrillo Zenteno; Iris Perez-Almeida; Fernando Javier Cobos Mora (AGRIVITA Journal of Agricultural Science, 2023)
Salinity affects 800 million hectares of agricultural soils in the world and represents a serious concern for crop production. The soils of the San Jacinto de Yaguachi canton (Guayas province, Ecuador), where rice has traditionally been grown with low yield, are characterized as saline. This research aimed to evaluate the agronomical performance and yield of five commercial rice varieties (INIAP FL-Arenillas, SFL 011, INIAP 14, INIAP 11, and Fedearroz 60) grown in a saline soil amended with leonardite (150 kg/ha). A randomized complete block design was used in a split-plot arrangement with three repetitions; the leonardite amendments corresponded to the main plot, and the rice varieties to the sub-plots. At harvest time, in the amended plots, increments in plant height, number of tillers, panicle number and length, number of grains per panicle, grain weight, and yield were obtained. Nutrient uptake also increased in the amended plants, with the sole exception of phosphorus, which responded poorly to the treatment. Under these conditions, it is concluded that the use of the leonardite amendment can be an effective practice for obtaining significantly higher rice production in saline soils.